2019
DOI: 10.22178/pos.49-4
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Effective Communication towards Performance of Construction Organization

Abstract: The purpose of this study is to examine the significant impacts of effective communication towards the performance of the construction organization. The objectives of the study include to identify impacts of effective communication and evaluate the degree of agreement to which effective communication influence construction organization from construction contractors and consultants' viewpoint. A sample of 200 construction contractors and consultants were randomly selected from the Bureau of Public Procurement (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…They go on to say that communication should exist at every hierarchy in an organization and should flow vertically both up and down the chains of command, horizontally to peers, co-workers and other departments, as well as diagonal when applied appropriately, such as going to one of your supervisors peers to ask for technical expertise. Effective communication is important because research has shown that effective communication in an organization can drive better performance of its members (Leje et al, 2019).…”
Section: Effective Communicationmentioning
confidence: 99%
“…They go on to say that communication should exist at every hierarchy in an organization and should flow vertically both up and down the chains of command, horizontally to peers, co-workers and other departments, as well as diagonal when applied appropriately, such as going to one of your supervisors peers to ask for technical expertise. Effective communication is important because research has shown that effective communication in an organization can drive better performance of its members (Leje et al, 2019).…”
Section: Effective Communicationmentioning
confidence: 99%
“…Some scholars in construction firms have explored the causes of performance heterogeneity based on adopted internal organizational factors (Geraldi, Lee and Kutsch, 2010;Zuhairy, et al, 2013). Many studies conclude that the effects of internal organizational factors on firms' performance are heterogeneous as some of the studies present positive impacts, while the other show negative impact (Lee, Kim and Lee, 2011;Yidizs, Basturk and Boz, 2014;Leje, Kasimu and Kolawole, 2019). These factors vary from study to study without being clear about why some studies emphasize some of them over others, though the findings are heterogeneous regarding whether the impact is direct or indirect (Ortega, Azorin and Cortes, 2010).…”
Section: Organizational Internal Factors and Construction Firm Performance Outcomesmentioning
confidence: 99%